2013
DOI: 10.1111/bij.12031
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlates of the distribution limits of two poeciliid species along a salinity gradient

Abstract: Identifying the environmental factors responsible for the formation of a species' distribution limit is challenging because organisms interact in complex ways with their environments. However, the use of statistical niche models in combination with the analysis of phenotypic variation along environmental gradients can help to reduce such complexity and identify a subset of candidate factors. In the present study, we used such approaches to describe and identify factors responsible for the parapatric distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…On small Caribbean islands that contain several poeciliid species (all of which became established by colonization as opposed to in situ speciation), a similar pattern is observed. On Trinidad and Tobago, the closely related P. reticulata and P. picta exhibit a parapatric distribution (Torres-Dowdall et al, 2013). Poecilia reticulata's range extension into lowland rivers seems to be limited by its relative intolerance of brackish and saltwater.…”
Section: Explanations For Patterns Of Native Species Richness On Carimentioning
confidence: 99%
See 1 more Smart Citation
“…On small Caribbean islands that contain several poeciliid species (all of which became established by colonization as opposed to in situ speciation), a similar pattern is observed. On Trinidad and Tobago, the closely related P. reticulata and P. picta exhibit a parapatric distribution (Torres-Dowdall et al, 2013). Poecilia reticulata's range extension into lowland rivers seems to be limited by its relative intolerance of brackish and saltwater.…”
Section: Explanations For Patterns Of Native Species Richness On Carimentioning
confidence: 99%
“…Poecilia reticulata's range extension into lowland rivers seems to be limited by its relative intolerance of brackish and saltwater. Poecilia picta is found across a wide range of salinities but its gradual disappearance in more upstream (freshwater) habitat seems to be driven by interspecific competition with P. reticulata (Torres-Dowdall et al, 2013). Likewise, on the island of Grenada there are two species of the same genus: P. reticulata and P. vivipara.…”
Section: Explanations For Patterns Of Native Species Richness On Carimentioning
confidence: 99%
“…In stream ecosystems, salinity, water velocity, temperature regimes, and dissolved oxygen are of particular importance1114. Other studies found interactions between biotic and abiotic variables to predict species distributions along environmental gradients3741, as exemplified by the study of Torres-Dowdall et al 42,. who examined ecological factors explaining the parapatric distribution of the congeners P. reticulata and P. picta in the lowlands of Trinidad.…”
mentioning
confidence: 99%
“…who examined ecological factors explaining the parapatric distribution of the congeners P. reticulata and P. picta in the lowlands of Trinidad. It appears as if the distribution of P. reticulata is limited by an abiotic factor (increasing salinity), whereas that of P. picta is limited by a biotic interaction (interspecific competition with P. reticulata )42.…”
mentioning
confidence: 99%
“…We assumed that competitive interactions for the focal species primarily occur with other species of the family Poeciliidae (Alberici da Barbiano et al . 2010; Torres-Dowdall et al . 2013) and that the intensity of competition is a function of the number of coexisting species.…”
Section: Methodsmentioning
confidence: 99%